Enhancing the activation of persulfate using nitrogen-doped carbon materials in the electric field for the effective removal of p-nitrophenol. Issue 60 (25th November 2021) - Tang, Mengdi; Zhang, Yonggang
Abstract : In the process of electro-activation of PDS by carbon cathode, PNP was removed from water mainly through SO4 ˙ − produced by cathode, ˙OH and 1 O2 produced indirectly, direct electron transfer and non-free radical oxidation of anode. Abstract : Degradation of nonbiodegradable organic compounds into harmless substances is one of the main challenges in environmental protection. Electrically-activated persulfate process has served as an efficient advanced oxidation process (AOP) to degrade organic compounds. In this study, we synthesized three nitrogen-doped carbon materials, namely, nitrogen-doped activated carbon plus graphene (NC), and nitrogen-doped activated carbon (NAC), nitrogen-doped graphene (NGE), and three nitrogen-doped carbon material-graphite felt (GF) cathodes. The three nitrogen-doped carbon materials (NC, NGE, NAC) were characterized using X-ray diffraction, Raman spectroscopy, X-ray electron spectroscopy, and nitrogen desorption–adsorption. The electron spin resonance technique was used to identify the presence of hydroxyl radicals (˙OH), sulfate radicals (SO4 ˙ − ) and singlet oxygen ( 1 O2 ) species. The results showed that NC was more conducive for the production of free radicals. In addition, we applied NC-GF to an electro-activated persulfate system with the degradation of p -nitrophenol and investigated its performance for contaminant degradation under different conditions. In general, the nitrogen-doped carbon electrode electro-activated persulfate process is a promising way to treat organic pollutants in wastewater.